The Compression Testing Apparatus of Border Material of Novel High Profile Insole to Control Pronation in Children with Flexible Flatfeet - Charoenvitvorakul, Thana (Thammasat University Hospital Journal Online, 2022)
Background: The gold standard of non-surgical treatment for flexible flatfeet is the UCBL (University of California Biomechanics Laboratory). However, children often times feel uncomfortable, such as skin redness pressing by high and hard border of device. Thus, the UCBL is less often prescribed because of the lowered compliance. An alternative treatment is an insole with arch support and appropriate supportive shoe. The problem of uniforms shoe is missing of firm heel counter and hard to find in the market. Even the good support one will be the high price. The researcher developed foot orthosis with a high border around the heel area call “High profile insole (HPI). The principle of HPI is the combination feature of total contact insole (TCI) and UCBL together in one device. This combo treatment might provide acceptable user compliance and corrective properties, combining both comfort and corrective properties. Objectives: The objective of this study is to evaluate stiffness of chosen materials for HPI’s border by evaluate deformation properties of this device configuration while loaded in a compression testing apparatus. Materials and Methods: The HPI’s border made by Podiaflex® 1.2 mm thickness attached together with Flexan® series1 0.53mm thickness. To test stiffness of device border in this study the pneumatic cylinder was connected to an air pressure regulator and air pump to perform pushing force to a paddle at the end of cylinder. To compare deformation volume at each corresponding force applied to the model shoe with HPI as well as deformation with the model shoe without the HPI. Results: Results is clear that a reduction deformation volume at medial side of shoe occurred in the HPI when force was applied, therefore the device had a reduction of more than 2 times that of deformation volume of model without HPI. This could be as a result of the material’s hardness and extra layers at the border areas reinforcing the heel part of model shoe to be stronger. Discussion and Conclusion: The heel counter of shoe and border of the HPI was designed to provide the same support to control over pronation of foot. The chosen materials were tested via mechanical testing to evaluate stiffness of the medial border of the device and observe changes of deforming volume. Result of this study evidenced an acceptable performance of the model shoe combined with the HPI, with an ability of the combo to tolerate various loading forces.